A/part: Writing retreats as spaces fostering a sense of belonging for academic staff (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
In June 2022, I attended a teaching and learning writing retreat with other early career researchers, the deputy dean of teaching and learning of the faculty, and the teaching and learning specialist for our faculty. I had recently completed my teaching portfolio as part of my probationary requirements and had been asked to join the retreat to guide and assist the other early career researchers who were working on their teaching portfolios at the time. At this specific retreat, we had quite a few frank discussions about our teaching and learning background experiences and we were given the space to be vulnerable and open with one another. At the time, I was working on a paper on student belonging, and I noted the parallel between what I was reading about student belonging and what I was experiencing at the retreat: a profound sense of being a part of a group, of belonging.